TINGKAT PENGETAHUAN COVID-19 BERHUBUNGAN DENGAN KECEMASAN PADA PENDERITA DIABETES MELLITUS - Zofir, Kusuma Mu’aedy; Setyorini, Andri (Coping: Community of Publishing in Nursing; Vol 10 No 3 (2022): Juni 2022DO - 10.24843/coping.2022.v10.i03.p03, 2022)
The very rapid increase in Covid-19 cases has caused unrest in the community. Psychological impact is starting to show from those who feel worried, panic, and stress. This is even more pronounced for people who have comorbid diseases, where they will be more susceptible to worsening conditions if infected with the Covid-19. The risk of death in people with diabetes mellitus due to Covid-19 is up to 50% higher than people without diabetes. This study aims to determine the relationship between the level of knowledge of Covid-19 and anxiety in people with diabetes mellitus. The research location was carried out in the Banguntapan II Community Health Center in Bantul. The research design is descriptive correlation using cross sectional approach. The sample in this study were 34 patients with diabetes mellitus using purposive sampling technique. The instrument used to measure the level of knowledge is the Covid-19 knowledge level questionnaire, while for anxiety using Hamilton Anxiety Rating Scale). Bivariate analysis using kendall tau test. The results showed that the level of knowledge of Covid-19 in people with diabetes mellitus was mostly in the high category as many as 31 respondents (91,2%) and anxiety in patients with diabetes mellitus was mostly in the moderate anxiety category as many as 28 respondents (82,4%). There is relationship between the level of knowledge of Covid-19 and anxiety in people with diabetes mellitus with correlation value of 0,483 and p value of 0,004 (<0,05).